ANALISIS PELAKSANAAN SISTEM DAN PROSEDUR PENATAUSAHAAN PENGELUARAN KAS DI KANTOR KECAMATAN MALALAYANG KOTA MANADO - Horman, Beybby C. (Jurnal Berkala Ilmiah Efisiensi, 2018)
Administration of cash disbursements in the regional apparatus work unit includes a series of processes and procedures : (1) provision of funds, (2) payment requests, (3) pay orders, (4) disbursements of funds, (5) accountability of the use of funds. The object of this research is Malalayang District Office. The purpose of this study is to analyze the adequacy of system and procedure administration of cash expenditure in the District Malalayang. The analytical method used is a descriptive method that aims to create a systematic, factual and accrual description of the facts, by comparing the system and expenditure procedures undertaken by the Malalayang District Office with Permendagri No. 59 of 2007. The results show that the Malalayang District Office has implemented cash dispensing system and procedures effectively and is in accordance with the Minister of Home Affairs Regulation No.59 of 2007.